Correlation of Biofilm Formation and Caco-2 Cell Attachment Properties in Colonization Ability of Acid-Bile Resistant Fecal Lactobacillus plantarum Isolates - Mahdi Rohani; Moslem Papizadeh; Mohammad Reza Pourshafie (Pasteur Institute of Iran, 2018)
Introduction: The strain-specific capabilities of lactobacilli are critical for gut colonization. In this study, we evaluated various colonization determinants of 42 fecal Lactobacillus plantarum isolates from the healthy human fecal samples. Methods: We investigated the attachment to the Caco-2 cell line, biofilm formation ability and cell surface activity of the isolates. Such properties were comparatively studied, and the regression between these features was statistically analyzed. Results: Among our results 18 (42.9%) were non-adhesive, 11 (26.2%) moderate adhesive and 13 (31%) strongly adhesive. The results showed that some isolates were significantly capable of biofilm formation. The highest rate of auto-aggregation was recorded for L. plantarum isolate RPR 240 (58%). Conclusion: Our results revealed a high degree of variability among colonization characteristics of the L. plantarum isolates indicating strain-specificity. Also, the colonization properties of the potential probiotic isolates had no significant correlation with each other. Our results confirmed the necessity of further in vivo colonization assays for selection of probiotic candidates.